Correlation between salivary interleukin‐6 levels and early locoregional recurrence in patients with oral squamous cell carcinoma: Preliminary study. Issue 6 (6th August 2012) - Sato, Jun; Ohuchi, Manabu; Abe, Keigo; Satoh, Takehiko; Abe, Takahiro; Yamazaki, Yutaka; Satoh, Akira; Notani, Ken‐ichi; Kitagawa, Yoshimasa
Abstract Background We have demonstrated that salivary interleukin‐6 (IL‐6) concentrations change during the treatment in patients with oral squamous cell carcinoma (OSCC). We sought to elucidate the correlations between salivary IL‐6 concentration and early locoregional recurrence in OSCC. Methods Stimulated saliva was collected before and after surgery from 27 consecutive patients with OSCC. Recurrence‐free survival (RFS) curves were plotted using the Kaplan–Meier method. Results Of the 27 patients, 11 (41%) were diagnosed with locoregional recurrence within 24 months postsurgery. The median concentrations of IL‐6 presurgery and postsurgery were 2.8 pg/mL and 2.1 pg/mL, respectively. The median postsurgery concentration of IL‐6 was significantly higher in patients with than without locoregional recurrence (p = .02). Multivariate analysis revealed that postsurgery salivary IL‐6 concentration was an independent risk factor for locoregional recurrence (p = .03; risk ratio, 0.14). Conclusions Posttreatment concentration of salivary IL‐6 may predict early locoregional recurrence in OSCC. © 2012 Wiley Periodicals, Inc. Head Neck, 2012